2009
DOI: 10.1007/s10824-009-9102-6
|View full text |Cite
|
Sign up to set email alerts
|

American Idol: should it be a singing contest or a popularity contest?

Abstract: American Idol , Committee, Contests, Tournaments, Voting, D23, D44,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…American Idol has not only produced such hugely successful entertainers as Carrie Underwood, Kelly Clarkson, and Jennifer Hudson--through gamified employee engagement during the talent search--and sold millions of albums--through gamified customer engagement leading to sales--but it has also created a highly profitable TV show by aligning the mechanics, dynamics, and emotions it developed for contestants with those developed for audience members (Amegashie, 2009;Ciulla et al, 2012;Meizel, 2011).…”
Section: Gamification At Work: the Case Of American Idolmentioning
confidence: 99%
“…American Idol has not only produced such hugely successful entertainers as Carrie Underwood, Kelly Clarkson, and Jennifer Hudson--through gamified employee engagement during the talent search--and sold millions of albums--through gamified customer engagement leading to sales--but it has also created a highly profitable TV show by aligning the mechanics, dynamics, and emotions it developed for contestants with those developed for audience members (Amegashie, 2009;Ciulla et al, 2012;Meizel, 2011).…”
Section: Gamification At Work: the Case Of American Idolmentioning
confidence: 99%
“…More recently, the resurgence of talent competitions has raised concerns about the possible extent of market failure due to short-termism in the management of talent and over-focusing on non-musical aspects of performers (Amegashie 2009;Zwaan and ter Bogt 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The economics studies that do exist on reality shows investigate the structure and rules of the contest. For example, Amegashie (2007) studied the allocation of voting rights between the expert judges and the viewers on "American Idol", designed to prevent low-ability contestants from winning. He showed that the contestants' differences in ability should be an important consideration in the allocation of voting rights.…”
Section: Introductionmentioning
confidence: 99%